Climate change alters the spatial pattern of plant spectral diversity across forest types - Peng, Yu; Xin, Jiaxun; Peng, Nanyi (Frontiers in Ecology and Evolution, 2023)
Species’ distribution, spatial distance and neighborhood interactions are among the important drivers for the global variation in species diversity. However, the responses of relationship between species’ spatial interaction and species diversity to climate change are still unknown. We applied 12 machine learning models to assess the responses of spectral diversity (indicate species diversity) of forests in 7 protected forest areas in China to the changes in 27 climate variables during two stages: 1990-2005 and 2005-2020. The results indicated that spectral diversity and intraspecific spatial distance had increased significantly under climate change. These also brought strong feedback to the variation in spectral diversity. Particularly, the contributions of neighboring interaction and plant-plant distance to the variation in species diversity between 1990-2000 was higher than those of climate change for all forest types. Our analyses revealed that species diversity, plant-plant interaction and spatial distance have closely associated with each other and sharply shifted under climate change. From this point of view, rather than community composition decomposition, spatial interaction analysis can give additional insights in understanding the mechanism of species diversity change under climate warming.